P. Ramlees music : an expression of local identity in Malaya during the mid-twentieth century - Chan Clare, Suet Ching (N/A, 2012)
P. Ramlees music : an expression of local identity in Malaya during the mid-twentieth century by Chan Clare, Suet Ching,